Prenatal diagnosis of homozygous alpha thalassaemia by direct DNA analysis of uncultured amniotic fluid cells. Issue 6427 (5th May 1984) - Chan, V; Ghosh, A; Chan, T K; Wong, V; Todd, D
Abstract : Prenatal diagnosis of homozygous alpha thalassaemia was performed in eight successive patients at risk using DNA from uncultured amniotic fluid cells. The presence of alpha gene was determined by restriction endonuclease mapping and hybridisation with cloned alpha and beta globin probes. This method is reliable and may be performed at 16 weeks of gestation.